2019
DOI: 10.1136/bmjopen-2019-031882
|View full text |Cite
|
Sign up to set email alerts
|

How far is too far? A nationwide cross-sectional study for establishing optimal hospital access time for Korean pregnant women

Abstract: ObjectivesAccess to a delivery unit is a major factor in determining maternal morbidity and mortality. However, there is little information about the optimal access time to a delivery unit. This study aimed to establish the optimal hospital access time (OHAT) for pregnant women in South Korea.DesignNationwide cross-sectional study.SettingWe used the National Health Insurance System database of South Korea.ParticipantsWe analysed the data of 371 341 women who had experienced pregnancy in 2013.Primary and second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
(17 reference statements)
0
4
0
1
Order By: Relevance
“…Travel time to the maternity hospital is a factor cited in the literature as important for carrying out adequate care management in a timely manner, reducing bad prognoses ( 22 ) . Greater distances and travel time may be associated with births that occur during the maternity hospital ( 23 ) as well as adverse birth outcomes, such as the need for admission to Intensive Care Units, postpartum transfusion, post-cesarean hysterectomy, among others ( 24 ) . In the USA, a cohort study carried out with a total of 662,245 birth records showed that greater distances to the birth hospital were associated with a greater risk of adverse maternal outcomes and admission to the Neonatal Intensive Care Unit ( 25 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Travel time to the maternity hospital is a factor cited in the literature as important for carrying out adequate care management in a timely manner, reducing bad prognoses ( 22 ) . Greater distances and travel time may be associated with births that occur during the maternity hospital ( 23 ) as well as adverse birth outcomes, such as the need for admission to Intensive Care Units, postpartum transfusion, post-cesarean hysterectomy, among others ( 24 ) . In the USA, a cohort study carried out with a total of 662,245 birth records showed that greater distances to the birth hospital were associated with a greater risk of adverse maternal outcomes and admission to the Neonatal Intensive Care Unit ( 25 ) .…”
Section: Discussionmentioning
confidence: 99%
“…O tempo de deslocamento até a maternidade é um fator citado na literatura como importante para realizar o manejo adequado da assistência em tempo hábil, reduzindo os maus prognósticos (22) . Maiores distâncias e tempo de deslocamento podem ter associação com nascimentos ocorridos ainda no percurso da maternidade (23) , bem como desfechos adversos no parto, como necessidade de admissão em Unidades de Terapia Intensiva, transfusão pós-parto, histerectomia pós-cesariana, entre outros (24) . Nos EUA, estudo de coorte realizado com um total de 662.245 registros de nascimento evidenciou que maiores distâncias até o hospital de parto foram associadas a maior risco de desfechos maternos adversos e internação em Unidade de Terapia Intensiva Neonatal (25) .…”
Section: Discussionunclassified
“…To shorten TIME 1, the accessibility of patients to obstetrical institutions should be assured. Indeed, several epidemiological studies about the relationship between maternal travel time and pregnancy complications have been reported 19,20,21 ; however, there is no report about the maternal travel time focused on perinatal outcomes in placental abruption. Recently, the consolidation of dispersed functions of public delivery facilities has been initiated all over Japan for the reform of future work systems of obstetric health care workers.…”
Section: Discussionmentioning
confidence: 99%